The Impact of Marketing-Like-Approach to Medical Specialist’s Decision for Giving Patient Recommendation to Palliative Care Unitin Haaj General Hospital Surabaya - Reswari, Putu Ayu Dhana (STRADA : Jurnal Ilmiah Kesehatan, 2020)
An objective of this study is to analyze the influence of marketing- like-approach and specialist psychological factors on the decision to send the patient to the Palliative Care Unit at Haaj General Hospital Surabaya. This study is observational-analytic. Samples taken were specialist who can send patients to the Palliative Care Unit in Haaj General Hospital. Determination of sampling is the stratified sampling method. The data analysis was done analytically by binary logistic regression. The results showed that psychological factors have no influence on the decision of sending patients to the Palliative Care Unit in Haaj General Hospital Surabaya. This research suggested Haaj General Hospital to resocializing against sending patients to the Palliative Care Unit in Haaj General Hospital Surabaya, held a question and answer session at the time resocializing, and considering a strategic placement for promotional media which easily seen by a specialist